2012
DOI: 10.3354/meps09910
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of European flounder life history patterns discloses alternatives to catadromy

Abstract: European flounder Platichthys flesus life history patterns were investigated in 3 basins along a latitudinal gradient (Minho, N Portugal; Gironde, SW France; Seine, N France). We used coupled Sr:Ca and Ba:Ca otolith signatures and microstructure to retrospectively determine habitats occupied by flounder during their life, including early larval ontogeny. Flounder exhibited high life history plasticity among and even within basins, apparent by the diversity of habitats used during larval ontogeny and throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 79 publications
1
14
1
1
Order By: Relevance
“…Common Snook in these areas may spawn over a more restricted period than at the inlet site (i.e., only when salinities are high enough) or they may be able to spawn in a wider range of salinities than previously believed. Maternal environment has been shown to affect salinity thresholds needed for egg buoyancy in other species [68] and similar adaptability to variable salinity habitats has been exhibited by the European Flounder [63]. If these areas are spawning habitat, then spawning site selection by Common Snook may involve trade-offs between habitat with consistently high salinity, allowing for more reproductive events within a year, and habitat that is less predictable but provides greater refuge and/or feeding opportunities.…”
Section: Discussionmentioning
confidence: 91%
“…Common Snook in these areas may spawn over a more restricted period than at the inlet site (i.e., only when salinities are high enough) or they may be able to spawn in a wider range of salinities than previously believed. Maternal environment has been shown to affect salinity thresholds needed for egg buoyancy in other species [68] and similar adaptability to variable salinity habitats has been exhibited by the European Flounder [63]. If these areas are spawning habitat, then spawning site selection by Common Snook may involve trade-offs between habitat with consistently high salinity, allowing for more reproductive events within a year, and habitat that is less predictable but provides greater refuge and/or feeding opportunities.…”
Section: Discussionmentioning
confidence: 91%
“…This result is principally verified by Paragamian & Wakkinen (2008) who reported multiple burbot movement patterns in a river-lake system of North America, using telemetry and limited sample size. For example, Daverat et al (2012) have shown that European flounder Platichthys flesus may spawn in coastal, brackish or freshwater environments, and multiple habitat use patterns exist. For example, Daverat et al (2012) have shown that European flounder Platichthys flesus may spawn in coastal, brackish or freshwater environments, and multiple habitat use patterns exist.…”
Section: Burbot Life Historymentioning
confidence: 99%
“…This result is principally verified by Paragamian & Wakkinen (2008) who reported multiple burbot movement patterns in a river-lake system of North America, using telemetry and limited sample size. Although widespread in salmonids (e.g., Thorpe 1994), it is only recently when such examples amongst nonsalmonid fish have emerged (Daverat et al 2006(Daverat et al , 2012Feutry et al 2012). For example, Daverat et al (2012) have shown that European flounder Platichthys flesus may spawn in coastal, brackish or freshwater environments, and multiple habitat use patterns exist.…”
Section: Burbot Life Historymentioning
confidence: 99%
“…All daily increment counts were made using a light microscope at 100× and 400× magnifications for the peripheral areas, and at 1000× magnification for the nucleus. Otolith microstructure was used to determine the duration of the different stages: pelagic (larval), metamorphosis (time period between first morphological asymmetry and the completion of juvenile features) and benthic (post-metamorphosis juveniles), in agreement with Geffen et al (2007) and Daverat et al (2012). The pelagic stage corresponded to the otolith nucleus, the metamorphic stage corresponded to the rings between the innermost and the outermost accessory primordia.…”
Section: Discussionmentioning
confidence: 99%